THE RELEVANCE OF JALALUDDIN RUMI'S SUFISM EDUCATION CONCEPT TO CHARACTER EDUCATION IN THE DIGITAL ERA - Arizul Suwar; Tb Endayani (Jurnal Sosial Humaniora Sigli, 2021)
This study aims to determine the concept of Sufism education according to Jalaluddin Rumi, and its relevance to character education in the digital era. The method used in this research is library research. Primary sources are Jalaluddin Rumi works, secondary sources are books and works that are relevant to the discussion of the concept of spiritual education. The data analysis technique uses content analysis method. The results of the discussion of this study indicate that education according to Jalaluddin Rumi is the ability to transcend everything that is born (visible) with the aim of obtaining the inner meaning behind it, related to character education. Rumi emphasizes education in the realm of spirituality (heart) because character is a reflection of the human heart. Facing a digital era marked by being fast and instantaneous, Rumi warns all of us not to forget the process, because something valuable can only be produced from a maximum process. On the other hand, Rumi also emphasized the importance of awareness, this is because character is marked by "one's attitude towards others", awareness here means being aware that other people are also human as they are God's creatures, meaning that they must be able to respect other people without any restrictions of identity.Keywords: Sufism Education, Jalaluddin Rumi, character education, the Digital Era